Identifying meaningful dietary intake and physical activity questions for individual and population health. Issue 3 (7th January 2021) - Shinall, Jennifer Bennett; Schlundt, David G.; Sullivan, Mikaela H.; Frank, Hannah J.; Po'e, Eli K.; Sommer, Evan C.; Bonnet, Kemberlee R.; Burgess, Laura E.; Barkin, Shari L.; Haws, Kelly L.
Summary: We aimed to identify valid screening questions for adults regarding physical activity and dietary behaviours that (a) were correlated with BMI, (b) were deemed by patients and providers to be relevant to clinical care, and (c) have utility for longitudinal understanding of health behaviours in populations. The goal was to identify screening questions that could be implemented at annual health care visits. First, we identified dietary behaviour questions and solicited patient input. Next, we tested both physical activity and dietary behaviour questions in a large sample to test their potential utility. Finally, we used cognitive interviews with patients and physicians to narrow our assessment for clinical settings. We present a parsimonious and reliable six‐question scale of physical activity and dietary behaviours for research settings, as well as a three‐question scale for clinical settings. We demonstrate a robust relationship between these measures and obesity. Additionally, we present evidence that these measures may serve as a useful red flag for patients before they develop obesity. We provide a concise and useful tool for assessing patients' physical activity and dietary behaviours in a variety of research settings. We also highlight the importance of incorporating this tool into the clinical intake flow for inclusion in patients' Electronic Health Record.